Spatial separation of replisome arrest sites influences homologous recombination quality at a Tus/Ter-mediated replication fork barrier. Issue 14 (17th July 2016) - Willis, Nicholas A.; Scully, Ralph
ABSTRACT: The Escherichia coli replication fork arrest complex Tus/ Ter mediates site-specific replication fork arrest and homologous recombination (HR) on a mammalian chromosome, inducing both conservative "short tract" gene conversion (STGC) and error-prone "long tract" gene conversion (LTGC) products. We showed previously that bidirectional fork arrest is required for the generation of STGC products at Tus/ Ter -stalled replication forks and that the HR mediators BRCA1, BRCA2 and Rad51 mediate STGC but suppress LTGC at Tus/ Ter -arrested forks. Here, we report the impact of Ter array length on Tus/ Ter -induced HR, comparing HR reporters containing arrays of 6, 9, 15 or 21 Ter sites—each targeted to the ROSA26 locus of mouse embryonic stem (ES) cells. Increasing Ter copy number within the array beyond 6 did not affect the magnitude of Tus/ Ter -induced HR but biased HR in favor of LTGC. A "lock"-defective Tus mutant, F140A, known to exhibit higher affinity than wild type (wt)Tus for duplex Ter, reproduced these effects. In contrast, increasing Ter copy number within the array reduced HR induced by the I-SceI homing endonuclease, but produced no consistent bias toward LTGC. Thus, the mechanisms governing HR at Tus/ Ter -arrested replication forks are distinct from those governing HR at an enzyme-induced chromosomal double strand break (DSB). We propose that increased spatial separation of the 2 arrested forks encountering an extended Tus/ Ter barrier impairs the coordination of DNA ends generated by the processing of the stalled forks, thereby favoring aberrant LTGC over conservative STGC.